817 Loss of Libido in A Man with An Incidental Leydig Cell Tumour Of the Testis: A Rare Tumour Discovered Following an Isolated Common Complaint. (12th October 2021) - Brown, D; Tsampoukas, G
Abstract: Introduction: Leydig cell tumours (LCTs) are rare testicular stromal neoplasms classically presenting with a painless testicular mass or swelling in adults. Symptoms secondary to hypogonadism may occur resulting from the hormonal activity of these tumours. Loss of libido is described in LCTs in conjunction with other symptoms; however, no case has reported this as the sole presenting feature. Case report: We describe the case of a 42-year-old man presenting to his General Practitioner with loss of libido and no other features suspicious of testicular cancer. Ultrasound performed due to an unrelated epididymal cyst detected an incidental mass confirmed as a benign LCT following radical orchidectomy. Biochemical markers remained normal throughout and following treatment his libido returned to normal. Conclusions: This case may serve as a reminder for clinicians to maintain a high index of suspicion for testicular neoplasms in patients with features of hypogonadism in the absence of classical features for testicular cancer.